Caixa Geral de Depósitos (Portugal) and TechnoLogica (Bulgaria): analysing companies' Corporate Social Responsibility in two European countries - Yordanova, D. (2017)
The studies in the area of Corporate Social Responsibility are very relevant to understand why companies are concerned with its implementation in the company. Besides, theoretical developments on this matter show that progressively companies are concerned about their performance on this subject and about reaching their objectives involving CSR. Corporate Social Responsibility should have self-regulating mechanisms through which the business would be monitored and companies should be ensure that law is guaranteed as far as ethical standards and international norms. According to the 2001 European Commission Green Paper, Social Responsibility conceptualization is associated with the idea of companies deciding, in a voluntary base, to contribute for a fair society and a cleaner environment. Caixa Geral de Depósitos (Portugal) and TechnoLogica (Bulgaria) are important companies concerned with the development of CSR activities and have some very interesting results in this area.